Multifactorial Determinants of Stunting among Under-Five Children in Tambun Tulang Village, South Coastal District, Indonesia - Hidayat, Hilda; Rahmaddian, Tosi; Hanum, Novia Zulfa; Mindayani, Sri; Rusti, Sukarsi (International Journal of Child Health and Nutrition, 2025)
Background: Stunting is a chronic condition of impaired growth in children under five, primarily due to long-term malnutrition. It is identified using the height-for-age (TB/U) indicator, where a Z-score below -2 standard deviations (SD) from the WHO child growth standards signifies stunting. In Kenagarian IV Koto Hilie, 53 children (8.32%) were recorded as stunted. Although malnutrition can begin during pregnancy or shortly after birth, it often becomes evident when the child reaches two years of age. Objective: This study aimed to identify the factors influencing the incidence of stunting among toddlers in Kampung Bukit Tambun Tulang. Methods: A quantitative, cross-sectional study design was employed. The population consisted of 173 toddlers, with a sample of 63 selected through simple random sampling. Primary data were collected via structured interviews using questionnaires, and secondary data were sourced from Kenagarian IV Koto Hilie health reports. Data analysis included univariate and bivariate methods, with the chi-square test employed to identify associations. Results: The study found that 57.1% of the sampled toddlers were stunted. Bivariate analysis revealed significant relationships between stunting and maternal knowledge (p = 0.003), family income (p = 0.022), and nutritious food intake (p = 0.016). Conclusion: Stunting is closely linked to maternal education, socioeconomic conditions, and child nutrition. Health workers should provide targeted education to promote behavioral change and improve parenting practices. Structured family coaching is recommended to support nutritional fulfillment and prevent stunting during early childhood development.